0216 Environmental bright light exposure is associated with sleep timing: the Multi-Ethnic Study of Atherosclerosis. (25th May 2022) - Clarkson-Townsend, Danielle; Rotter, Jerome; Rich, Stephen; Redline, Susan; Sofer, Tamar
Abstract: Introduction: Light influences sleep via the circadian system, but few studies have examined objective light exposure and sleep outcomes in the general population. We investigated the relationship between daily average time above 1, 000 lux white light (TALT1000), a proxy for outdoor light exposure, and actigraphy measures of sleep timing and regularity in the Multi-Ethnic Study of Atherosclerosis (MESA). Methods: Light and actigraphy data collected over 5+ days (wrist-worn Actiwatch Spectrum) were analyzed. Relationships between TALT1000 and dichotomized sleep timing measures (sleep midpoint regularity, defined as <30 minutes variability in sleep timing; late sleep onset, defined as 12AM or later) were evaluated with logistic regression models, adjusted for age, self-reported race/ethnicity, sex, federal poverty level, partner status, employment, smoking, BMI, depression score, sleep duration, day length by month and site, chronotype, number of days measured, ActiWatch off-wrist time, and average physical activity during active period. Stratified analyses for employment status and sleep duration were also conducted. Covariates associated with quartiles of TALT1000 were evaluated with ordinal logistic regression. Results: 2, 135 MESA participants with valid actigraphy data were included (mean age=68.6 years, 53.8% female, mean TALT1000=61 minutes, mean sleep midpoint variability=70.6 minutes). There was a dose-response relationship between quartiles of TALT1000 and sleep timing regularity, with participants in the highest quartile of TALT1000 exposure (equivalent to 90+ minutes daily bright light exposure) having 87.7% increased odds of sleep timing regularity (adjOR=1.88, CI=1.35-2.62); the highest quartile of TALT1000 was also associated with a 41% decreased odds of sleep onset timing ≥12AM (adjOR=0.59, CI=0.43-0.81). Age, race/ethnicity, partner status (single), and day length were negatively associated, while BMI, sex (male), earlier chronotype, and physical activity were positively associated with quartiles of TALT1000 (p<0.05). Conclusion: Greater average bright light exposure is associated with greater sleep timing regularity and earlier sleep onset in a large sample of U.S. adults. Future analyses will investigate timing of light exposure and associated multi-omic signatures. Support (If Any): NIH-NHLBI T32HL007901, R35HL135818, R01HL098433, R24HL114473, 75N92019R002.